(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This research was conducted to determine the reasons and expectations of tennis players participating in the Eastern League organized by the tennis federation, preferring this sports branch. The research group consists of 138 athletes (53 women and 85 men) participating in the Eastern League Tennis Tournament. The scanning method was used in the research. As a data collection tool, a personal information form prepared by taking expert opinions and a scale form determining the reasons for preferring the tennis branch were used. SPSS statistical package program was used to analyze the data, and the significance was accepted as p<0.05. According to the results of the research, the research group; 73.9% are students, 39.9% are undergraduates, 56.5% are members of a club other than a tennis club, 55.8% do their training at Provincial Directorates of Youth and Sports, and 60%, It has been determined that 1 of them has a provincial championship. In addition, most of the athletes stated that the materials in the sports facilities were insufficient. It was seen that the friends, easy access to the facilities and prevalence, family and TV, cinema, and press-broadcasting were effective in preferring the tennis branch of the research group, respectively.